Prevalence, maternal characteristics, and birth outcomes of preeclampsia: A cross-sectional study in a single tertiary healthcare center in greater Kuala Lumpur Malaysia - Sutan, Rosnah; Aminuddin, Nurul Afzan; Mahdy, Zaleha Abdullah (Frontiers in Public Health, 2022)
Preeclampsia is associated with an increased risk of adverse maternal and perinatal outcomes. This study aimed to assess preeclampsia prevalence in a Malaysian referral maternity hospital and the association between preeclampsia and maternal characteristics and outcomes. A cross-sectional study was conducted between January 2010 and December 2020 using secondary data from a single tertiary healthcare center in Greater Kuala Lumpur, Malaysia. A total of 40,212 deliveries were included for analysis to investigate the association between conditions and preeclampsia. The reported prevalence of preeclampsia was 1.6%. Pregnant women with preeclampsia had a higher risk of preterm delivery (67.7%), cesarean delivery (70.7%), neonatal low birth weight (48.5%), neonatal 5-min Apgar score < 7 (18.1%), and neonatal intensive care unit (NICU) admission (19.8%). There were significantly higher odds of developing preeclampsia among nulliparae (adjusted odd ratio [adjOR] 1.792, 95% CI: 1.518–2.115), previous history of preeclampsia (adjOR 5.345, 95% CI: 2.670–10.698) and multiple pregnancies (adjOR 1.658, 95% CI: 1.071–2.566). There was a significant association when a combination of variables for risk assessment: the presence of anemia and gestational hypertension effect on preeclampsia (OR 26.344, 95% CI: 9.775–70.993 (p<0.002) and gestational hypertension without anemia on preeclampsia (OR 3.084, 95% CI: 2.240–4.245 (p<0.001). Similarly, an association was seen between chronic hypertension and younger age (<35 years old) on preeclampsia (OR 14.490, 95% CI: 9.988–21.021, p<0.001), and having chronic hypertension with advanced maternal age (≥35 years old) on preeclampsia (OR 5.174, 95% CI: 3.267–8.195, p<0.001). Both conditions had increased odds of preeclampsia, in varying magnitudes. Pregnant women with preeclampsia had significantly higher odds for preterm delivery (adjOR 6.214, 95% CI: 5.244–7.364), caesarean delivery (adjOR 4.320, 95% CI: 3.587–5.202), low birth weight (adjOR 7.873, 95% CI: 6.687–9.271), Apgar score < 7 (adjOR 3.158, 95% CI: 2.130–4.683), and NICU admission (adjOR 8.778, 95% CI: 7.115–10.830). Nulliparity, previous history of preeclampsia, and multiple pregnancies were associated with an increased risk of preeclampsia. The presence of different underlying conditions, such as chronic hypertension, anemia, and extremes of maternal age played an important role in increasing preeclampsia risk in the considered study. Larger samples are needed to validate such findings.